The Survey of Prevalence of Aphthous Oral Ulceration by Patient’s Self Report in 12- to 18-Years Old Thai Students in Srinakharinwirot Prasarnmitr Demonstration School - รังสิยานนท์ สรสัณห์; วัชโรทยางกูร เปี่ยมกมล; ตลึงจิตร สินีภัทร์ (Srinakharinwirot University Dental Journal (E-ISSN 2774-0811), 2014)
การสำรวจความชุกของแผลแอพทัสในช่องปากโดยการรายงานจากผู้ป่วยเด็กไทย อายุ 12-18 ปี ณ โรงเรียนสาธิตแห่งมหาวิทยาลัยศรีนครินทรวิโรฒ ประสานมิตร Aphthous ulceration is one of the most common oral lesions affecting the non-keratinized epithelium of the oral cavity. There are three forms of aphthous ulceration; minor, major, and herpetic forms. The etiologies of this lesion are still unknown but it can be categorized in the group of the autoimmune diseases. The objective of the present study was to investigate the individual awareness of aphthous ulceration among Srinaharinwirot Prasnrnmitr Demonstration School students who have age rang form 12-18 years old. Three hundred and seventy two students of the school form Mattayom 1 to 6 were included in the survey. Each subject was individually interviewed during the annual oral examination supported by the Faculty of Dentistry, Srinakharinwirot University. Data related to the occurrence of aphtous ulceration, frequency, and location of the lesion were obtained and analyzed. There were 156 males (41.9%) and 216 females (58.1%), age ranged from 12-18 years (average age = 14.5 years) in the current investigation. Ninety one percent of the subjects reported about experience of aphthous ulceration in the oral cavity. The most frequency of the incidence of the lesion was 3 times per year (16.2%) The lesions mostly occurred solitarily with the major attacked site at left and right sides of lower labial and vestibular mucosa (16.7%). From Yate’s correction Chi-square analysis, there was no relationship between gender factor and the occurrence of aphthous ulceration (p = 0.176). The present study showed that the survey of prevalence of aphthous oral ulceration by patient self report is practical and less time consuming for large population. However, quality of analysis may not be all valid. The current result can be used as the preliminary data for further study of aphthous ulceration in adolescence. Keywords: Awareness, Aphthous ulceration, Thai children, Adolescent, Survey, Prevalence